Qualitative and Quantitative Analysis on Fibrates - A Spectroscopic Study - Gunasekaran, S.; Renuga Devi, T.S.; Sakthivel, P.S. (Asian Journal of Chemistry, 2010)
In the present work, qualitative and quantitative analyses were made on the lipid lowering drugs namely gemfibrozil and fenofibrate through the means of infrared, Raman and UV-Visible spectroscopy. Some specific modes of vibration are identified and the absorbance values are noted under the different conditions of exposure. The ratios of absorbance among some specific modes of vibration are calculated, which represents the internal standards. The sets of internal standards of these drugs are compared with suitable storage conditions to check whether any change has taken place due to the exposure. Also a systematic approach has been adopted using UV-Visible spectroscopic method to study the light absorption activity under different storage conditions and the interaction of these drugs with some of the trace elemental constituents such as sodium, potassium, calcium, iron and lead ions. The study of interaction of drug with these ions reveals the nature of bonding, affinity of ion with drug molecules. The estimation of the active substance of a drug is an important quantitative analysis. The method of assay is experimented with these drugs using UVVisible spectroscopic measurements.